2020
DOI: 10.5999/aps.2019.01473
|View full text |Cite
|
Sign up to set email alerts
|

The Exoscope versus operating microscope in microvascular surgery: A simulation non-inferiority trial

Abstract: Background The Exoscope is a novel high-definition digital camera system. There is limited evidence signifying the use of exoscopic devices in microsurgery. This trial objectively assesses the effects of the use of the Exoscope as an alternative to the standard operating microscope (OM) on the performance of experts in a simulated microvascular anastomosis.Methods Modus V Exoscope and OM were used by expert microsurgeons to perform standardized tasks. Hand-motion analyzer measured the total pathlength (TP), to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…No comparative studies were able to clarify the differences between these two technologies at this time. Two pre‐clinical studies have tried to compare the OE and the OM in performing microvascular anastomoses 21,22 . These studies demonstrated the non‐inferiority of the OE, but no clear differences and recommendations were drawn.…”
Section: Discussionmentioning
confidence: 99%
“…No comparative studies were able to clarify the differences between these two technologies at this time. Two pre‐clinical studies have tried to compare the OE and the OM in performing microvascular anastomoses 21,22 . These studies demonstrated the non‐inferiority of the OE, but no clear differences and recommendations were drawn.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional microscopes have, however, several limitations, including limited focal range, image quality, portability, and especially in terms of ergonomics [11,15]. Surgeons stand and operate in uncomfortable positions during surgery, because they need to fix their eyes to the eyepieces of the microscopes [13,15] (see Figure 1 (a)). Moreover, the surgeons use either a mouth switch or handgrips to constantly adjust the view of the microscopes [2].…”
Section: Background 21 Microscopes Versus 3d Exoscopesmentioning
confidence: 99%
“…It enables surgeons to perform surgeries in a heads-up position which eases their neck and back pain and all surgical members to easily follow a surgical procedure by watching a 3D screen. Most research has investigated the impact of the 3D exoscopes on a primary surgeon's performance in terms of its technical (e.g., image quality, lighting, magnification) and surgical aspects (e.g., optics, ergonomics, maneuverability of instruments) [11,13,15]. Beyond the benefits to surgeons, this state-of-the-art technology is also expected to improve communication between surgical team members during surgery, because people in an operating room (OR) can easily follow a surgical procedure and have the same view with the primary surgeon by watching a 3D screen [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…The exoscope system is composed of a scope positioned outside of the body cavity such that a high-definition (HD) view of the surgical field is projected onto a two-dimensional (2D) or 3D high-resolution monitor. Recent efforts to preserve stereopsis as well led to the development of the 3D exoscope system [ 4 ]. The gradual application of the 3D exoscope system in a multitude of neurosurgical procedures such as cranial and spinal surgeries has suggested that it is a safe and effective alternative to the OM [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%